2019
DOI: 10.1002/jpln.201800647
|View full text |Cite
|
Sign up to set email alerts
|

Glacially abraded rock flour from Greenland: Potential for macronutrient supply to plants

Abstract: Rock flour (RF) is a fine‐grained material produced naturally by glacial movement and resulting bedrock abrasion. In Greenland fluvial transported RF from the inland ice sheet sediments in riverbeds and marine outflows. This fine‐sized RF (50% < 9.8 µm) has a high reactivity and may therefore potentially be used to rejuvenate nutrient poor soils and provide nutrients to plants. The aim of this study was to evaluate the ability of a RF from Greenland to supply P, K, Mg, and S to plants. A double‐pot system was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The experiment showed that GRF-application had no significant impact on the biomass production. This is consistent with pot trial experiments with ryegrass [15]. Little effect was found on above and below ground biomass using glacial rock flour from Greenland, even though the applied amount of GRF was 5% of the soil weight (corresponding to an application rate of 30 t GRF ha −1 ).…”
Section: Discussion Implications and Conclusionsupporting
confidence: 83%
See 4 more Smart Citations
“…The experiment showed that GRF-application had no significant impact on the biomass production. This is consistent with pot trial experiments with ryegrass [15]. Little effect was found on above and below ground biomass using glacial rock flour from Greenland, even though the applied amount of GRF was 5% of the soil weight (corresponding to an application rate of 30 t GRF ha −1 ).…”
Section: Discussion Implications and Conclusionsupporting
confidence: 83%
“…The δ 15 N values in the AGB reflected the proportion of 15 N vs. 14 N in the plant tissue (Figure 6c). As seen, T3 and T4 tended to have a lower 15 N abundance than T1 and T2, though with only T3 being significantly different from both T1 and T2. The δ 13 C values (Figure 6d) represented the ratio of 13 C/ 12 C in the AGB.…”
Section: Biomass Response To Treatmentsmentioning
confidence: 72%
See 3 more Smart Citations